Diagnosis and clinical significance of Human bocavirus 1 in children hospitalized for lower acute respiratory infection: molecular detection in respiratory secretions and serum. Issue 10 (27th October 2022) - Colazo Salbetti, Maria Belen; Boggio, Gabriel Amilcar; Abbiatti, Giuliana; Montañez Sandoz, Agustina; Villarreal, Veronica; Torres, Erika; Pedranti, Mauro; Zalazar, Jose Alberto; Moreno, Laura; Adamo, Maria Pilar
Abstract : Introduction. Human bocavirus 1 (HBoV1) infection occurs with viral genome presence in respiratory secretions (RS) and serum, and therefore both samples can be used for diagnosis. Gap statement. The diagnostic sensitivity of HBoV1 DNA detection in serum and the duration of DNAaemia in severe clinical cases have not been elucidated. Aim. To determine HBoV1 DNA in serum and RS of paediatric patients hospitalized for lower acute respiratory infection (LARI) and to analyse the clinical–epidemiological features of positive cases. Methodology. This was a prospective, transverse study. Physicians selected the clinical situations and obtained paired clinical samples (RS and serum) that were tested by PCR/qPCR for HBoV1. Positive cases were analysed considering time of specimen collection, co-detection, clinical manifestations and viral load; statistical significant level was set at α=0.05. Results. HBoV1 was detected in 98 of 402 cases included (24 %); 18/98 (18 %) patients had the virus detectable in serum and 91/98 (93 %) in RS ( P <0.001). Positivity rates were not significantly different in patients with RS and serum collected within or beyond 24 h of admission. Single HBoV1 infection was identified in 39/98 patients (40 %), three patients had HBoV1 in both clinical samples (3/39, 8 %) and 32 (32/39, 82 %) only in RS, 22 of them (69 %) with both clinical samples within 24 h of admission. Cough ( P =0.001) and rhinitis ( P =0.003) were significantly frequent among them and most patients were diagnosed with bronchiolitis (22/39, 56 %) and pneumonia (9/39, 23 %), which was more frequent compared to cases with co-infection ( P =0.04). No significant differences were identified among patients with high, medium or low viral load of HBoV1 regarding rate of positivity in both clinical samples, the time of collection of RS and serum, co-detection, first episode of LARI, clinical manifestations, comorbidity or requirement for assisted ventilation. Intensive care unit (ICU) patients had a significantly higher frequency of detection ( P <0.001) and co-detection ( P =0.001) compared to patients on standard care. Conclusions. HBoV1 is prevalent among infant patients hospitalized for LARI and including it in the standard testing can add to the aetiological diagnosis in these cases, especially for patients admitted to the ICU. HBoV1 detection in serum did not contribute significantly to the diagnosis as compared to detection in respiratory secretions.